Pengaruh Kepuasan Pengguna Sistem Informasi Terhadap Kinerja Pegawai (Studi Kasus UPTB Kantor Samsat Panda) - Irawan, Mauladen; Sudaryanti, Dwiyani; Mahsuni, Abdul Wahid (e_Jurnal Ilmiah Riset Akuntansi, 2024)
The purpose of this study is to see the impact of user satisfaction of the information system on the performance of UPTB officers of Samsat Panda Office. The population in this survey is the UPTB officials of Panda Bureau Samsat. This research is included in the quantitative method because it uses primary data. For this method of research it is a method of data collection using queries or surfers and data collection techniques using questionnaires. The sample was taken from a population using probability sampling and for the data sample is from 25 respondents from UPTB Officer Samsat Panda. The results of this study, which is based on the testing of the hypothesis on the t test, show that the hypothetical (H1) states that user satisfaction of the information system has a positive and significant impact on staff performance. Keywords: Information system user satisfaction, official performance